P010 QUALITATIVE EVALUATION OF PATIENT PERSPECTIVES REGARDING IBD&ME (IBDANDME.ORG), A NOVEL ONLINE BIOLOGIC DECISION AID FOR PATIENTS WITH INFLAMMATORY BOWEL DISEASE. (7th February 2019) - Chen, Michelle S; Sidorkiewicz, Stephanie; Conovitz, Samuel; Almario, Christopher; Lasch, Karen; Ursos, Lyann; Shklovskaya, Julia; Spiegel, Brennan
Abstract: Background: Navigating the risk-benefit profiles of the various biologic options approved for inflammatory bowel disease (IBD) can be challenging for patients who are considering biologic therapies as a treatment option. We created an online patient decision aid called IBD&me (ibdandme.org) to clarify individual patient preferences about biologic therapies and encourage more active involvement in decision making. It includes an educational component and an interactive exercise with a series of ratings tasks that generates a personalized preferences report for patients to share and discuss with their physician. In this study, we aimed to assess the tool by soliciting patient input on IBD&me. Methods: We conducted a series of in-depth interviews with IBD patients referred from an academic IBD center. Using a retrospective probing technique, participants first navigated through the website on their own while interviewers took notes. This was followed by an interview session where participants were asked about their experience using IBD&me. Sessions were audio-recorded, and screen displays were captured to explore patient-system interactions. Usability was measured using the System Usability Scale (SUS; 0-100; higher scores = higher usability). Three researchers coded the transcripts using ATLAS.ti and performed a thematic analysis of the interviews. Results: We interviewed 12 IBD patients, 10 of whom were biologic-experienced, with a mean age of 41 ± 16 years. It took participants 28.3 ± 12.9 minutes on average to complete IBD&me. The mean SUS score was 79.3 ± 14.2 (90th percentile), and 11 patients indicated they were likely to recommend IBD&me to another IBD patient. Thematic analysis uncovered strengths and shortcomings related to various usability domains, as well as insight into patients' personal perspectives and experiences, including disease burden, decision making around medications, and relationship with their physician (Table 1). This led us to identify opportunities to enhance IBD&me not only to improve functionality, but also to reframe existing content so it is more relevant to patients. In particular, we made an effort to put technical explanations in the context of individual disease and treatment journeys (Figure 1). Conclusion: The SUS score suggests excellent usability for the preliminary version of IBD&me. However, the results from our qualitative analysis indicate an opportunity to refine the website for improved patient-centered design. This highlights the need to engage would-be end users during development of patient decision aids to reduce potential discordance between researcher and patient perspectives and best meet patient expectations. Next, we plan on conducting additional interviews with biologic-naïve patients using the updated version of IBD&me to deepen our understanding of patient decision making prior to initiation of biologics. Table 1. Sampling of themes identified during analysis of patient interviews Figure 1. Example page of revisions made to IBD&me based on patient feedback